2003
DOI: 10.1515/cclm.2003.142
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine Alterations in the Aging Male

Abstract: The recent increase in the elderly population, current health trends and awareness of age-related changes in the male endocrine system, have led to discussions about the role of the hormonal changes in the aging process in males. Better prevention and treatment of suboptimal health status and age-related diseases in aging men are based on an improved understanding of aging, particularly of the significance of age-associated hormonal changes. The aims of this study were 1) to evaluate the age dependence of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
37
1
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(51 citation statements)
references
References 24 publications
12
37
1
1
Order By: Relevance
“…Hence as with Caucasians, serum TT, DHEAS, IGF-1, IGFBP-3 and ADT declined progressively with age, SHBG, PSA and free PSA increased progressively with age while prolactin showed no appreciable change with age [11] . Furthermore, the percentage difference in the levels of the hormones between 15-to 19-year-olds compared to 70-to 79-year-olds is about the same for all parameters between Caucasians and Kuwaitis [11] . For example, in Germans, Elmlinger et al [11] showed that the difference in serum testosterone level between a 15-to 19-and 70-to 79-yearold German is about 20.9%, while in Kuwaitis it is 20.7% (p !…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Hence as with Caucasians, serum TT, DHEAS, IGF-1, IGFBP-3 and ADT declined progressively with age, SHBG, PSA and free PSA increased progressively with age while prolactin showed no appreciable change with age [11] . Furthermore, the percentage difference in the levels of the hormones between 15-to 19-year-olds compared to 70-to 79-year-olds is about the same for all parameters between Caucasians and Kuwaitis [11] . For example, in Germans, Elmlinger et al [11] showed that the difference in serum testosterone level between a 15-to 19-and 70-to 79-yearold German is about 20.9%, while in Kuwaitis it is 20.7% (p !…”
Section: Discussionmentioning
confidence: 65%
“…Furthermore, the percentage difference in the levels of the hormones between 15-to 19-year-olds compared to 70-to 79-year-olds is about the same for all parameters between Caucasians and Kuwaitis [11] . For example, in Germans, Elmlinger et al [11] showed that the difference in serum testosterone level between a 15-to 19-and 70-to 79-yearold German is about 20.9%, while in Kuwaitis it is 20.7% (p ! 0.11).…”
Section: Discussionmentioning
confidence: 77%
“…It means that the overall daily amount of hormone secretion increases. In elderly people the inhibiting effect of cortisol on the hypothalamic-pituitary axis is frequently impaired [101,102]. Diagnostic test results also show impaired cortisol suppression in response to dexametazone, as well as decreased cortisol secretion in response to ACTH [89].…”
Section: Cortisolmentioning
confidence: 99%
“…Zwiększeniu ulega więc całkowita pula wydzielania tego hormonu w ciągu doby. U osób w wieku podeszłym często dochodzi do upośledzenia hamującego działania kortyzolu na oś podwzgórzowo-przysadkową [101,102]. Stosując testy diagnostyczne stwierdzono również upośledzoną supresję kortyzolu w odpowiedzi na deksametazon, a także zmniejszone wydzielanie kortyzolu w odpowiedzi na ACTH [89].…”
Section: Kortyzolunclassified
“…It is known that age-related glucose intolerance is often associated with insulin resistance (24). Furthermore, other hormones related to muscle protein turnover alter with age (25). Therefore, the physiological changes with age may influence the difference of response to myofibrillar pro tein degradation after feeding.…”
mentioning
confidence: 99%